Epidural Anesthesia in Abdominal Surgery - N. S. Smolin; K. N. Khrapov (Вестник анестезиологии и реаниматологии)
The epidural anesthesia has found widespread application in abdominal surgical interventions. But the relevance of its use is the subject to some doubt and discussion in connection with developing surgical technologies and reduction of the degree of surgical aggression, and introduction of new approaches to the management of patients in the perioperative period. Often the risks of epidural anesthesia exceed expected benefits. This is a limiting factor for its use. Today, there is no uniform approach to the way epidural analgesia is administered in the intraoperative period. However, there is a correlation between the frequency of adverse events related to epidural block and the route of administration (speed of administration, volume, and concentration).Therefore, selecting the optimal method of epidural analgesia within the framework of combined anesthesia can minimize the risks and maximize its positive effects in abdominal surgery.